2022
DOI: 10.1186/s13014-022-02012-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of AI-driven prediction models to realize real-time tumor tracking during radiotherapy

Abstract: Background In infrared reflective (IR) marker-based hybrid real-time tumor tracking (RTTT), the internal target position is predicted with the positions of IR markers attached on the patient’s body surface using a prediction model. In this work, we developed two artificial intelligence (AI)-driven prediction models to improve RTTT radiotherapy, namely, a convolutional neural network (CNN) and an adaptive neuro-fuzzy inference system (ANFIS) model. The models aim to improve the accuracy in predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Zhou Dejun et al observed that the regression-based prediction model does not represent the tumor motion accurately. CNN-driven prediction models were found to outperform the regression-based prediction model [29]. This paper proposes a Kinect v2 3D camera scheme driven by time-series deep-learning algorithmic models that can improve the accuracy of real-time tumor motion prediction compared with the regression model.…”
Section: Classification and Prediction Performance For Pseudopatient-...mentioning
confidence: 99%
“…Zhou Dejun et al observed that the regression-based prediction model does not represent the tumor motion accurately. CNN-driven prediction models were found to outperform the regression-based prediction model [29]. This paper proposes a Kinect v2 3D camera scheme driven by time-series deep-learning algorithmic models that can improve the accuracy of real-time tumor motion prediction compared with the regression model.…”
Section: Classification and Prediction Performance For Pseudopatient-...mentioning
confidence: 99%